Influence of recovery manipulation after hyperlactemia induction on the lactate minimum intensity - Ribeiro, L. F. P.; Gonçalves, C. G. S.; Kater, D. P.; Lima, M. C. S.; Gobatto, C. A. (European Journal of Applied Physiology, 2009)
This study analyzed the influence of recovery phase manipulation after hyperlactemia induction on the lactate minimum intensity during treadmill running. Twelve male runners (24.6 ± 6.3 years; 172 ± 8.0 cm and 62.6 ± 6.1 kg) performed three lactate minimum tests involving passive (LMTP) and active recoveries at 30%vVO2max (LMTA30) and 50%vVO2max (LMTA50) in the 8-min period following initial sprints. During subsequent graded exercise, lactate minimum speed and VO2 in LMTA50 (12.8 ± 1.5 km/h and 40.3 ± 5.1 ml/kgmin) were significantly lower (P < 0.05) than those in LMTA30 (13.3 ± 1.6 km/h and 42.9 ± 5.3 ml/kgmin) and LMTP (13.8 ± 1.6 km/h and 43.6 ± 6.1 ml/kgmin). In addition, lactate minimum speed in LMTA30 was significantly lower (P < 0.05) than that in LMTP. These results suggest that lactate minimum intensity is lowered by active recovery after hyperlactemia induction in an intensity-dependent manner compared to passive recovery.